The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s0317167100017327
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Predictors in Acute Basilar Artery Occlusion

Abstract: 368Basilar artery occlusion (Bao) is an infrequent form of acute ischemic stroke (aiS). this particular type of stroke occurs in approximately 1% of all-cause cases and is reported in approximately 8% of patients with symptomatic vertebrobasilar territory ischemia.1,2 Basilar artery occlusion symptoms are heterogeneous and may vary from mild neurological deficits consisting of visual, oculomotor, and behavioral abnormalities to a locked-in state or coma.3,4 however, severe and persistent ABSTRACT: Objective: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…These findings are consistent with our previous study in posterior-circulation strokes due to BA occlusion; higher NIHSS at the time of treatment, longer time to treatment and arterial hypertension were identified as independent negative predictors of favorable clinical outcome [17]. Likewise, the ASPECT score [18], older age, stroke severity and a history of diabetes mel litus were identified as negative predictors of good clinical outcome in posterior-circulation strokes [19].…”
Section: Resultssupporting
confidence: 91%
“…These findings are consistent with our previous study in posterior-circulation strokes due to BA occlusion; higher NIHSS at the time of treatment, longer time to treatment and arterial hypertension were identified as independent negative predictors of favorable clinical outcome [17]. Likewise, the ASPECT score [18], older age, stroke severity and a history of diabetes mel litus were identified as negative predictors of good clinical outcome in posterior-circulation strokes [19].…”
Section: Resultssupporting
confidence: 91%
“…To the best of our knowledge, this is the largest single-center series assessing the safety and clinical outcome of IVT for PCS. Most of the previously published studies evaluating the safety and efficacy of IVT for PCS had small sample sizes (range, 9–84 patients), they assessed ICH using a different definition of SICH, or they investigated acute basilar artery occlusion only (1,1217).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the largest single-center series assessing the safety and clinical outcome of IVT for PCS. Most of the previously published studies evaluating the safety and efficacy of IVT for PCS had small sample sizes (range, 9-84 patients), they assessed ICH using a different definition of SICH, or they investigated acute basilar artery occlusion only (1,(12)(13)(14)(15)(16)(17). The rate of PCS among IVT-treated patients (12•8% in the present study) is lower than that reported in the non-IVT population (20-26%) (18,19), which may have several reasons: Initial symptoms such as vertigo or diplopia are misinterpreted or even neglected by the patients, prolonging time to treatment and possibly excluding patients from IVT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional endovascular treatment should be started as soon as possible and not considered only as a rescue strategy (57, 58). Data from two small series on basilar artery occlusion patients (52, respectively 70 patients) reported better 90-day clinical outcomes in patients treated with bridging (59, 60).…”
Section: Ivt In Posterior Circulation Strokementioning
confidence: 98%